STRATEGI PENINGKATAN PROFITABILITAS PADA PT. BANK KERTA RAHARJA CABANG BANJARAN - Agung, Taufiq; Ikhsan Rizqi , Nugraha; Iis, Farida; Regita, Ameylia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This study intended to identify the profitability level of PT. Bank Pengkreditan Rakyat Kerta Raharja Banjaran and also identify the efforts made by PT. Bank Pengkreditan Rakyat Kerta Raharja Banjaran in increasing profitability. The analytical method used is through the measurement of the level of profitability for the last three years using the Return on Assets (ROA) and Return on Equity (ROE) formulas. Based on the results of our research obtained from the field, it shows that the level of profitability using the Return on Assets (ROA) method has decreased every year, can be seen in 2016 of 12.36% while in 2017 amounted to 9.61% while in 2018 experienced a decrease of 0.87% to 8.74%.